MG53 as a Novel Therapeutic Protein to Treat Acute Lung Injury. (25th January 2021) - Whitson, Bryan A; Mulier, Kristine; Li, Haichang; Zhou, Xinyu; Cai, Chuanxi; Black, Sylvester M; Tan, Tao; Ma, Jianjie; Beilman, Greg J
ABSTRACT: Introduction: Lung injury has several inciting etiologies ranging from trauma (contusion and hemorrhage) to ischemia reperfusion injury. Reflective of the injury, tissue and cellular injury increases proportionally with the injury stress and is an area of potential intervention to mitigate the injury. This study aims to evaluate the therapeutic benefits of recombinant human MG53 (rhMG53) protein in porcine models of acute lung injury (ALI). Materials and Methods: We utilized live cell imaging to monitor the movement of MG53 in cultured human bronchial epithelial cells following mechanical injury. The in vivo efficacy of rhMG53 was evaluated in a porcine model of hemorrhagic shock/contusive lung injury. Varying doses of rhMG53 (0, 0.2, or 1 mg/kg) were administered intravenously to pigs after induction of hemorrhagic shock/contusive induced ALI. Ex vivo lung perfusion system enabled assessment of the isolated porcine lung after a warm ischemic induced injury with rhMG53 supplementation in the perfusate (1 mg/mL). Results: MG53-mediated cell membrane repair is preserved in human bronchial epithelial cells. rhMG53 mitigates lung injury in the porcine model of combined hemorrhagic shock/contusive lung injury. Ex vivo lung perfusion administration of rhMG53 reduces warm ischemia-induced injury to the isolated porcine lung. Conclusions: MG53 is an endogenous protein that circulates in the bloodstream. Therapeutic treatment with exogenous rhMG53 may be part of a strategy to restore (partially or completely) structural morphology and/or functional lung integrity. Systemic administration of rhMG53 constitutes a potential effective therapeutic means to combat ALI.